Field measurements of indoor and community air quality in rural Beijing before, during, and after the COVID‐19 lockdown. (27th August 2022) - Li, Xiaoying; Baumgartner, Jill; Harper, Sam; Zhang, Xiang; Sternbach, Talia; Barrington‐Leigh, Christopher; Brehmer, Collin; Robinson, Brian; Shen, Guofeng; Zhang, Yuanxun; Tao, Shu; Carter, Ellison
Abstract: The coronavirus (COVID‐19) lockdown in China is thought to have reduced air pollution emissions due to reduced human mobility and economic activities. Few studies have assessed the impacts of COVID‐19 on community and indoor air quality in environments with diverse socioeconomic and household energy use patterns. The main goal of this study was to evaluate whether indoor and community air pollution differed before, during, and after the COVID‐19 lockdown in homes with different energy use patterns. Using calibrated real‐time PM2.5 sensors, we measured indoor and community air quality in 147 homes from 30 villages in Beijing over 4 months including periods before, during, and after the COVID‐19 lockdown. Community pollution was higher during the lockdown (61 ± 47 μg/m 3 ) compared with before (45 ± 35 μg/m 3, p < 0.001) and after (47 ± 37 μg/m 3, p < 0.001) the lockdown. However, we did not observe significantly increased indoor PM2.5 during the COVID‐19 lockdown. Indoor‐generated PM2.5 in homes using clean energy for heating without smokers was the lowest compared with those using solid fuel with/without smokers, implying air pollutant emissions are reduced in homes using clean energy. Indoor air quality may not have been impacted by the COVID‐19 lockdown in rural settings in China and appeared to be more impacted by the household energy choice and indoor smoking than the COVID‐19 lockdown. As clean energy transitions occurred in rural households in northern China, our work highlights the importance of understanding multiple possible indoor sources to interpret the impacts of interventions, intended or otherwise.